AGRARIAN REFORM IN THE CONTEXT OF INCREASING POOR PEASANTS' ACCESS TO LAND TENURE IN INDONESIA - Tobing, Anggiat; Praptono, Seno Tri; Hestiono, Pramu; Pattinasarany, Eva Berta (Fakultas Hukum Universitas Swadaya Gunung Jati, 2024)
The development of Indonesian society has a goal, as stated in paragraph IV of the Preamble to the 1945 Constitution of the Republic of Indonesia, then from that to form an Indonesian State Government that protects the entire Indonesian nation and all of Indonesia's bloodshed. Article 33 Paragraph (3) of the 1945 Constitution of the Republic of Indonesia states that the earth and water and the natural resources contained therein are controlled by the state and used for the greatest prosperity of the people. In connection with demands for reform in all areas of development, the People's Consultative Assembly in 2001 issued Decree Number IX/MPR/2001, concerning Agrarian Reform and Natural Resources Management, and MPR RI Decree Number 5/MPR/2003, concerning assignments to MPR Leaders to Convey Suggestions on the Implementation of MPR Decisions by the President, DPR, Supreme Court, BPK. Basic Agrarian Law Number 5 of 1960 as the basis for national land law which is based on Article 33 paragraph (3) of the 1945 Constitution of the Republic of Indonesia, the land provisions are aimed at achieving social justice for the entire community in relation to the acquisition and utilization of resources. natural resources, especially land. Agrarian reform or Agrarian Reform as an issue is complex and multidimensional, which is a major program of the Indonesian state in realizing the welfare of the Indonesian people, especially in terms of increasing poor farmers' access to land control in Indonesia, but in implementing agrarian reform, this is not an issue. which is easy, there are many obstacles, both from legal, land administration, social, political, cultural and security aspects.